Empathy Level among Dental Students of Bangladesh Utilizing the Cambridge Behavior Scale - Mainul Haque (Journal of Global Pharma Technology, 2017)
Background: Empathy is the capacity to appreciate what another individual is feeling and suffering from within the other individual's setting or orientation, i.e., the capacity to accommodate individuality in another's shoes. Thereafter, empathy permits an individual to intermingle efficiently in the community. Then empathy acts as superglue of the universes of discourse, pulling us to support others and end from hurting others. Methods: This was a cross sectional study. The study populations were Dental students of Dhaka Dental College and Mandy Dental College, Dhaka, Bangladesh. Data was collected early part of 2017. The universal sampling method was adopted. Cambridge Empathy Scale Questionnaire was utilized for the data collection. Results: There was no statistically significant (p=0.079) difference observed in empathy level between male (38±9.1) and female (39.8±8.6). However statistically significant (p<0.001) differences were observed between public and private dental schools. The study found that 83.4% (297) and 16.6% (59) of SP had good and poor level empathy respectively. Conclusions: Empathy is imperative in the physician-patient rapport. Females scored higher empathy level than their male counterparts.  Additionally, empathy level was higher in Year-I than other years of study.Keywords: Empathy, Dental Students, Bangladesh.